TEACHING THE ACCURATE PRONUNCIATION AND DISTINCTION OF THE UZBEK SOUNDS “X” AND “H” TO ENGLISH LEARNERS - Do‘smamatova Lola (Modern American Journals, 2025)
This study aims to explore suitable methods for teaching English students who learn Uzbek to accurately and properly produce the Uzbek sounds “x” and “h”. Since these two sounds are not phonetically open and do not exist in English phonetics, students who learn Uzbek may find the pronunciation of these two sound really difficult at first. Actually, not only foreign learners, but also native speakers of Uzbek may be confused if they are not familiar with the proper rules and techniques to pronounce “x” and “h”. For reasons above, this paper explores effective methods for teaching and learning the two Uzbek phonemes.
Keywords: Phonology, pronunciation, experimental phonetic method, descriptive analysis, comparative analysis, glottal fricative, velar fricative.